Scoring the score the role of the orchestrator in the contemporary film industry - Sapiro, Ian (New York Routledge, Taylor & Francis Group, 2017)
Scoring the Score' is the first scholarly examination of the orchestrator's role in the contemporary film industry. Orchestrators are crucial to the production of a film's score, yet they have not received significant consideration in film-music research. This book sheds light on this often-overlooked yet vital profession. It considers the key processes of orchestrating and arranging and how they relate, musical and filmic training, the wide-ranging responsibilities of the orchestrator on a film-scoring project, issues related to working practices, the impact of technology, and the differences between the UK and US production processes as they affect orchestrators.
Interviews and interviewees -- Orchestrating and arranging -- Becoming an orchestrator -- The impact of technology -- Involvement in a film-scoring project -- Working practices -- Local differences in a global industry -- The role of the orchestrator in the contemporary film industry -- Appendix A: outline interview schedules -- Appendix B: interviewee details -- Appendix C: information on software packages.
Includes index.
Keywords: Motion picture music -- Production and direction; Instrumentation and orchestration